Minimally Invasive Palmaris Longus Abductorplasty for Severe Carpal Tunnel Syndrome. Issue 4 (December 2017) - Chung, Sze-Ryn; Yap, Robert Tze-Jin; Tuck, Andrew Yam Kean
Abstract : Camitz abductorplasty is the most commonly used tendon transfer in patients with severe carpal tunnel syndrome with significant muscle wasting and loss of opposition. This procedure requires a long incision in the palm to harvest a strip of palmar aponeurosis to lengthen the palmaris longus tendon, allowing it to reach the abductor pollicis brevis insertion. Several complications have been attributed to this extensive dissection in the palm. We describe a minimally invasive palmaris longus abductorplasty using a strip of free flexor carpi radialis tendon graft to achieve the necessary length. This can be done together with carpal tunnel release in patients with severe carpal tunnel syndrome.